2016
DOI: 10.1016/j.jdent.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel non-invasive reinforcement of MOD cavities on endodontically treated teeth

Abstract: A B S T R A C TObjectives: To evaluate the biomechanical influence of reconnecting the buccal and lingual walls of endodontically treated lower molar with a large MOD cavity. Methods: 3D models were created from a micro-CT scan of an extracted intact lower human molar. Finite element analysis was then used to compare the stress distribution and displacement of the structures between different models: Unrestored MOD on ETT (Unrest), MOD on ETT restored with composite resin (Norm), MOD on ETT reinforced with a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Connecting the remaining opposing cavity walls can be also accomplished circumferentially covering the rebuilt mesial and/or distal walls, a technique called "wallpapering" by Deliperi and colleagues (Deliperi et al, 2017). So far, to use of FRC materials to circumferencially connect the walls of MOD cavities was only attempted by Daher et al (2016), but they performed this externally, around the coronal part of the teeth. In our study, when applied circumferentially, there was no difference between the fibre glass net and polyethylene fibres.…”
Section: Groupmentioning
confidence: 99%
“…Connecting the remaining opposing cavity walls can be also accomplished circumferentially covering the rebuilt mesial and/or distal walls, a technique called "wallpapering" by Deliperi and colleagues (Deliperi et al, 2017). So far, to use of FRC materials to circumferencially connect the walls of MOD cavities was only attempted by Daher et al (2016), but they performed this externally, around the coronal part of the teeth. In our study, when applied circumferentially, there was no difference between the fibre glass net and polyethylene fibres.…”
Section: Groupmentioning
confidence: 99%
“…Mandibular molars were chosen for this test to be in agreement with the first study that first described this technique [14]. In that mentioned study, the authors propose two possible configurations of placing the fiber-reinforced strip: in a regular ring shape surrounding the crown or in a modified ring with the fibers crossing in the middle of the cavity in an "X" shape.…”
Section: Discussionmentioning
confidence: 99%
“…Cuspal deflection was shown to induce micro-cracks due to cyclic bending loads and the limited elasticity of dental hard tissues [23]. The FEA study that first evaluated the effect of non-invasively reinforcing MOD cavities with a fiber-reinforced strip [14], showed a reduction of cuspal deflection. It also showed that the stress values in the cervical area of ring-reinforced teeth were lower compared to normal restorations, by redirecting that stress into the fiber bundle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the results of another FEA study demonstrated that reconnecting buccal and lingual walls of an endodontically treated lower molars with a 2 mm wide FRC band modeled as ring around the middle of the crown has a positive effect on stress distribution, reduces stress concentration at the cavity wall-restorative material interface and enhances fracture resistance [35].…”
Section: Discussionmentioning
confidence: 99%